2022
DOI: 10.3390/cancers15010151
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Exercises for Cancer-Related Fatigue among Women with Breast Cancer: A Systematic Review and Network Meta-Analysis

Abstract: Context: Cancer-related fatigue (CRF) is the most common cause of physical powerlessness in women with breast cancer (BC). The practice of continuous effective exercise is beneficial with respect to reducing CRF. Objective: To explore exercise efficacy and respective ranks with respect to reducing CRF in women with BC within the inter-treatment and post-treatment periods. Methods: Throughout this systematic review and network meta-analysis, articles published from 2000 to March 2022 were included. Article sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…Even though, none of the BEGYN-1 study patients showed any sign of overexertion or other negative side effects of too much physical activity, further research is needed to individualize recommendations for the level of physical activity to aim for (50, 51). The increased physical activity and fitness achieved in the BEGYN-1 study might have multiple other consequences that are known to be associated with increased physical activity in breast cancer patients, e.g., increased bone health (52), reduced cancer related fatigue (53), and reduced cancer related cognitive impairment (54). Strengths of our study are the high number of patients, the inclusion prior to therapy induction, the dual assessment of physical activities by using a fitness tracker and a diary, and the long follow up period of one year.…”
Section: Discussionmentioning
confidence: 99%
“…Even though, none of the BEGYN-1 study patients showed any sign of overexertion or other negative side effects of too much physical activity, further research is needed to individualize recommendations for the level of physical activity to aim for (50, 51). The increased physical activity and fitness achieved in the BEGYN-1 study might have multiple other consequences that are known to be associated with increased physical activity in breast cancer patients, e.g., increased bone health (52), reduced cancer related fatigue (53), and reduced cancer related cognitive impairment (54). Strengths of our study are the high number of patients, the inclusion prior to therapy induction, the dual assessment of physical activities by using a fitness tracker and a diary, and the long follow up period of one year.…”
Section: Discussionmentioning
confidence: 99%
“…For cancer-related fatigue in women with BC, yoga, aerobic resistance, and aerobic yoga are recommended as inter- and post-treatment exercises to improve their physical resilience and quality of life in the long run [ 172 ].…”
Section: Modulation Of the Microbiota Through Diet As A Potential Adj...mentioning
confidence: 99%
“…Network meta-analysis (NMA), also called meta-analysis of mixed treatment comparisons or multiple treatment comparisons (20), offers a method to compare the size of the impact of various intervention types on CRF in patients with breast cancer by estimating direct and indirect comparisons. Although two previously published NMA studies were identified (21,22), the study only reported on the effects of various exercise interventions, and no further studies were conducted on other intervention types. Consequently, this study aims to conduct an NMA on relevant randomized controlled trials (RCTs) to compare the effects of various interventions on CRF in patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%